TINAGL1 promotes hepatocellular carcinogenesis through the activation of TGF-β signaling-medicated VEGF expression - Sun L (Cancer Management and Research, 2019)
Lu Sun,1,2 Zihui Dong,3 Hongli Gu,2 Zhixian Guo,2 Zujiang Yu2 1Department of Gastroenterology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, China; 2Department of Infectious Disease, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, China; 3Department of Precision Medicine Center, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, China Background and purpose: Tubulointerstitial nephritis antigen-like 1 (TINAGL1) is an extracellular matrix protein that plays an important role in cell adhesion and therefore modulates cell proliferation, migration, and differentiation. In addition, it is frequently upregulated in highly metastatic tumors. The aim of our study was to determine the role of TINAGL1 in the progression and metastasis of hepatocellular carcinoma (HCC).Materials and methods: TINAGL1 mRNA levels were analyzed in HCC and adjacent nontumorous samples by reverse transcription polymerase chain reaction (RT-PCR). Human HCC cell lines were transfected with lentiviral plasmids expressing either si-TINAGL1 or TINAGL1 and subjected to CCK-8, colony forming, transwell migration, Annexin V/propidium iodide, and 5-ethynyl-2′-deoxyuridine uptake assays. Suitably transfected HCC cells were injected into athymic nude mice to establish xenograft tumors that were imaged and measured on a weekly basis. Mediators of the TGF-β signaling pathway were analyzed by Western blot.Results: TINAGL1 was upregulated in human HCC tissues and associated with poor prognosis. TINAGL1 knockdown suppressed HCC cell growth, proliferation, and migration and induced apoptosis in HCC cells, whereas TINAGL1 overexpression had opposite effects. In addition, inhibition of TINAGL1 retarded xenograft tumor growth in a nude mouse model. Mechanistically, TINAGL1 activated the TGF-β signaling pathway and increased VEGF secretion.Conclusion: TINAGL1 promotes hepatocellular carcinogenesis and metastasis via the TGF-β/Smad3/VEGF axis and is a potential new biomarker of HCC.Keywords: TINAGL1, LCN7, hepatocellular carcinoma, TGF-β, VEGF